The microbiological efficacy on the basis of hyaluronidase in patients with chronic endometritis and uterine myoma - N A Troshina; I I Dolgushin; V F Dolgushina; L I Bakhareva; I V Kurnosenko; T V Nadvikova (IP Berlin A.V., 2015)
The goal of our study was to evaluate the effectiveness of microbilogical use of Longidaza in the treatment of active nonspecific endometritis in women with uterine myoma. By a random sample they were divided into two groups of women. The first comprised patients with active chronic endometritis were treated with standard causal antibiotic therapy. The second group included patients, who had an additional Longidaza to standard therapy. It was found that the women surveyed both in the first and second groups predominantly found non plasmacoagulating staphylococci, enterococci and anaerobes. Application of Longidaza in combination with antibiotic therapy leads to a significant improvement in most of the microbial landscape of the cervical canal and uterine cavity, which is confirmed by microbiological methods of investigation.